Efficacy of fungicide tebuconazole in barley varieties with different resistance level - Sooväli, Pille; Koppel, Mati (MTT Agrifood Research Finland, 2010)
Efficacy of the fungicide tebuconazole was tested in 2 treatment regimes in 3 spring barley varieties over three years (2003 2005). The impact of the fungicide on the control of major barley pathogens Pyrenophora teres and Cochliobolus sativus, as well as kernel yield was studied in the course of field trials. The fungicide treatments had a strong impact on the control of infection of P. teres and increased kernel yield in variable disease infection conditions. For the more resistant genotype, fungicide application had relatively low returns because of the much higher level of biological resistance and small disease-related yield reductions. For the susceptible genotype, severe disease infection caused bigger yield reduction, not compensated by the use of fungicides. Use of fungicide demonstrated the highest economic return in the case of the moderately susceptible barley variety.
Keywords: Ka; spring barley; net and spot blotch; tebuconazole; application time; yield; quality